Cheap Labour or Formative Experience during COVID-19: Observational Perspectives on Pharmacy Student Co-op Placements - Alison Starkey (Canadian Society for Studies in Education, 2020)
In this snapshot of current research, modifications and reformulations of initial questions regarding the role of the pharmacy student and the nature of their co-op placement are emerging from observations and experiences on the frontlines of the COVID-19 pandemic. Shifting healthcare contexts necessitate an examination of pharmacists' reflections on their work experiences prior to, during and post COVID-19. This pivot in research direction is discussed in light of the pandemic and evolving healthcare situation. As such, the discussion encompasses: scope of practice changes, feminization, core competencies, preceptor-student relationships, the role of lifelong learning as developed through experiential co-op student placements, the impact of work intensification on students' learning and the accessibility of pharmacists as frontline healthcare workers engaged in public health education. Against the stark relief of the pandemic, examining co-op placements as formative experience or cheap labour may serve to further elucidate the nature of the pharmacy profession's transformation.